Effect of pollination on rapeseed (Brassica campestris L. var. Toria) production in Chitwan, Nepal - Pudasaini, R; Thapa, RB (Journal of Agriculture and Environment, 2014)
Rapeseed is an important cash crop of Nepal and an experiment was conducted to study the effect of pollination on its production in Chitwan during 2012-2013. The experiment was designed in Randomized Complete Block with four replications and five pollination treatments. The rapeseed plots were caged with mosquito nets at 10% flowering except natural pollination. Two-framed colonies of Apis mellifera L. and Apis cerana F. were introduced separately for pollination, and control plot caged without pollinators. Seed set increased by 48.72% with Apis cerana F. and 45.73% with Apis mellifera L. pollination as compared to the control. The highest seed yield was obtained from Apis cerana F. (1.11 mt/ha), followed by Apis mellifera L. (0.88 mt/ha), hand (0.75 mt/ha), natural pollination (0.66 mt/ha) and control (0.13 mt/ha), respectively. This study clearly indicated pollination deficit under natural condition, and therefore, management of honeybee is necessary for higher production and productivity of rapeseed under Chitwan condition.